Test-Retest Reliability of Vibration Perception Threshold Test in People with Type 2 Diabetes Mellitus - Domínguez-Muñoz, Francisco Javier (Int J Environ Res Public Health, 2020)
Background: Diabetes mellitus is a chronic disease characterized by fasting hyperglycemia. It affects approximately 415 million people worldwide and involves a variety of complications. One of them is the loss of sensitivity to peripheral vibration. Objective: Our study aims to discover the test-retest reliability of a procedure for assessing vibration sensitivity in people with type 2 diabetes mellitus. Methodology: 90 people with type 2 diabetes mellitus (56 men and 34 women) performed the vibration perception threshold (VPT) test using the Vibratron II device. A re-test was completed seven days after the first reading. Results: The relative reliability of the VPT test result is excellent (intraclass correlation coefficient = 0.96). The same applies to gender and obesity subgroups. Regarding absolute reliability, the standard error of measurement is 8.99%, and the small real difference is 24.94%. Conclusions: The relative and absolute reliability results of the vibration perception threshold in people with type 2 diabetes mellitus offer excellent results.